2018
DOI: 10.1111/sji.12643
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell cross‐reactivity may explain the large variation in how cancer patients respond to checkpoint inhibitors

Abstract: The therapeutic use of the immune system to specifically attack tumours has been a long-standing vision among tumour immunologists. Recently, the use of checkpoint inhibitors to turn-off immunosuppressive signals has proven to be effective in enhancing T-cell reactivity against patient-specific neoantigens, resulting from somatic mutations. Several of the identified T-cell epitopes share similarity with common bacterial and viral antigens, suggesting the involvement of pre-existing microbial cross-reactive T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 73 publications
(181 reference statements)
0
20
0
Order By: Relevance
“…In some occasions, bacterial antigen-reactive T cells might cross-react with tumour antigens, leading to tumour cell destruction. 80 While the exposure of HSPCs to microbiota-derived compounds is important for the generation of educated mature innate immune cells to fight pathogens and even tumours, unfortunately, the activation of innate and adaptive immunity by commensal bacteria might trigger autoimmunity. 81 The highly homologous protein sequences between the human and microbial proteins suggest that certain autoantibodies and/or autoreactive T cells in autoimmune diseases are derived from the host immunity against bacteria.…”
Section: Compounds Regulate Haematopoiesismentioning
confidence: 99%
“…In some occasions, bacterial antigen-reactive T cells might cross-react with tumour antigens, leading to tumour cell destruction. 80 While the exposure of HSPCs to microbiota-derived compounds is important for the generation of educated mature innate immune cells to fight pathogens and even tumours, unfortunately, the activation of innate and adaptive immunity by commensal bacteria might trigger autoimmunity. 81 The highly homologous protein sequences between the human and microbial proteins suggest that certain autoantibodies and/or autoreactive T cells in autoimmune diseases are derived from the host immunity against bacteria.…”
Section: Compounds Regulate Haematopoiesismentioning
confidence: 99%
“…However, a high TMB does not always predict responders to iCPI therapy, which might be due to neoantigen heterogeneity and an extremely diverse array of somatic mutations (106, 107). It is noteworthy that T cell epitopes have a similarity to bacterial and viral antigens suggesting a cross reactivity of T cells to intestinal bacterial and viral antigens, which can also modulate the iCPI therapy (108). In addition, PD-L1 expression can be controlled by driver mutations and oncogenic signaling (109112).…”
Section: Immune Modulatory Molecules and Their Relevance For T Cell Rmentioning
confidence: 99%
“…This considerable immune redundancy exists to cover the deficit between the predicted number of MHC-bound antigenic peptide epitopes that humans encounter during their lifetime (~10 12 ) versus the number of unique TCRs available in the periphery (<10 8 ) ( Mason, 1998 ; Wucherpfennig, 2004 ; Sewell, 2012 ). A biologically relevant consequence of cross-reactivity where infection with an initial microbe alters immunity to subsequent, non-related infecting pathogen - termed heterotypic immunity ( Gil et al, 2015 ) - has been reported to influence the course of natural infections in humans ( Aslan et al, 2017 ), and can also affect vaccine-mediated immunity and immune-mediated checkpoint therapy outcomes in vivo ( Sioud, 2018 ). Where such cross-reactivity narrows the immune response and/or skews the enrichment of non-protective immune responses, sub-optimal immunity following infection or post-vaccination can result ( Clute et al, 2005 ; Aslan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%